PRIVACY, FACE, AND SOCIAL RESPECTABILITY IN A DIGITAL CHINA - Ollier-Malaterre, Ariane (AoIR Selected Papers of Internet Research, 2021)
This study attempts to delineate $2 when they use social media, shop online, and make electronic payments using WeChat Pay and Alipay. It is part of a book I am writing on perceptions of privacy and surveillance in China and is grounded in an inductive content analysis of 58 semi-structured in-depth interviews I conducted late 2019 in Beijing, Shanghai, and Chengdu. Privacy is written with two different words in Mandarin: $2 (a personal thing you do not wish to disclose in public akin to Western definitions) and $2 (hiding a shameful secret). Most of my interviewees used the latter meaning: $2 . Privacy, thus, was $2 , understood as $2 (moral face - e.g., purchases of personal medicine, underwear and sex-related products, or weapons) and $2 (social face - eg., financial information). Moreover, they perceived the need to hide shameful information $2 : parents and supervisors, or hackers who would disclose personal information, but less so an abstract entity such as the government. For instance, several interviewees felt they could “hide on Weibo” using a pseudonym, despite the real-name registration policy. These findings on privacy may shed slight on how Chinese citizens view the digitalization of surveillance through facial recognition monitoring and the building of the social credit system, and contribute to culture-sensitive surveillance research.